Transformation of arsenic species from seafood consumption during in vitro digestion - Liu, Bei; Sui, Jianxin; Feng, Ruixue; Lin, Hong; Han, Xiangning; Sun, Xun; Cao, Limin (Frontiers in Nutrition, 2023)
Arsenic (As) species analysis is important for the risk evaluation of seafood. Until now, there has been limited information on the change of As species during digestion. Here, the As species in different types of seafood before and after in vitro digestion were investigated. Although inorganic As was not detected in digested fish samples, As(V) contents in digested crabs and scallops were 17.12 ± 1.76 and 138.69 ± 7.53, respectively, which were approximately 2–3 times greater than those of the pre-digestion samples. In further experiments, arsenocholine, dimethylarsinate, arsenobetaine, and monomethylarsonate were all convertible to As(V) during in vitro digestions with different rates. The transformation demonstrates a complex process and could be affected by many factors, such as pH, time, and digestion juice composition, of which pH seemed to be particularly important. Free radicals were responsible for the oxidation in the transformation reactions. Unlike arsenobetaine, arsenocholine seemed to be able to directly transform to monomethylarsonate without the intermediate dimethylarsinate. This study reveals and validates the potential of other species (oAs or/and unknown species) to convert to iAs, identifies the main factors affecting this process, and proposes a reaction pathway. There is an important implication for promoting a more accurate risk assessment of arsenic in foodstuffs.